REASURANSI DALAM PERSPEKTIF MAQASHID AL-SYARI’AH - Moh. Ulumuddin; Ahmad Insya' Ansori (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2021)
Background. Reinsurance is a type of international business. As an international business, reinsurance companies have a global scope and operations. Important issues that need to be discussed in this study include how to conceptually study reinsurance in Indonesia? this problem can be solved through a normative approach, the second problem relates to how is reinsurance in the perspective of maqhasid al-syari'ah? This problem can be solved through a philosophical approach, by looking for a common thread between the concept and practice of reinsurance itself.Methods. This research is a library research. The approach in this research uses philosophical-theology by positioning Shari'ah insurance in a theological context and Maqasid al-Shari'ah in a philosophical context. Operationally, the first approach is used to explore the legal basis, technical guidelines to the aspects of implementing Sharia Insurance in Indonesia. The second approach is used to draw a common thread between reinsurance and Maqasid al-Shari'ah, content analysis techniques, namely studying messages in various literatures ranging from vocabulary, sentence patterns and background situations.Results. In terms of investment, insurance companies as the holder of the trust must invest the funds collected and the investment must be carried out in accordance with sharia. In the management of investment funds, both tabarru' and saving, a Wakalah bil Ujrah contract can be used by following the provisions as above, the Mudharabah contract by following the provisions of the Mudharabah fatwa. reinsurance as the subject of the fulfillment of the delegation of responsibility given by the cending company to the second insurer even though in essence there is a Quota Share both profit and risk. The most important aspect lies in the reinsurance agreement itself.